2014
DOI: 10.1017/jfm.2014.297
|View full text |Cite
|
Sign up to set email alerts
|

Discrete-vortex method with novel shedding criterion for unsteady aerofoil flows with intermittent leading-edge vortex shedding

Abstract: Unsteady aerofoil flows are often characterized by leading-edge vortex (LEV) shedding. While experiments and high-order computations have contributed to our understanding of these flows, fast low-order methods are needed for engineering tasks. Classical unsteady aerofoil theories are limited to small amplitudes and attached leading-edge flows. Discrete-vortex methods that model vortex shedding from leading edges assume continuous shedding, valid only for sharp leading edges, or shedding governed by ad-hoc crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
224
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
2
2

Relationship

2
4

Authors

Journals

citations
Cited by 232 publications
(281 citation statements)
references
References 66 publications
(75 reference statements)
15
224
2
Order By: Relevance
“…This flow feature signals the formation of the shear layer in which there is an eruption of surface flow into the mainstream. As in previous work [58,60], the instant when the spike in the negative C f region first reaches the zero value is taken as the time corresponding to initiation of LEV formation. In Fig.…”
Section: Identification Of Lev Initiation From Cfd Datamentioning
confidence: 99%
See 1 more Smart Citation
“…This flow feature signals the formation of the shear layer in which there is an eruption of surface flow into the mainstream. As in previous work [58,60], the instant when the spike in the negative C f region first reaches the zero value is taken as the time corresponding to initiation of LEV formation. In Fig.…”
Section: Identification Of Lev Initiation From Cfd Datamentioning
confidence: 99%
“…They demonstrated that for flows around a given airfoil operating at a given Reynolds number, LEV shedding is always initiated at a critical value of the LESP [59] and is independent of motion kinematics, provided that LEV formation is not preceded by significant trailing-edge separation. Additionally, Ramesh et al [58] developed a novel low-order numerical solver, called LDVM, for 2D low Re unsteady flows, using the LESP to predict and modulate LEV shedding. In the LDVM, when the instantaneous value of LESP exceeds a predetermined critical value, LEV shedding is modeled by shedding a discrete vortex at each time step of the numerical method.…”
Section: Introductionmentioning
confidence: 99%
“…al 36 that the initiation and termination of leading-edge vorticity shedding is determined by a nondimensional measure of the suction at the leading edge. It has also been shown that this leading edge section parameter (LESP) is the same as leading coefficient A 0 in the Fourier series representing the bound vorticity.…”
Section: Lesp Criterion For Initiation Of Lev Formation Lev Shedding mentioning
confidence: 99%
“…Katz 18 has developed a discrete-vortex method for separated flow past an airfoil, where the location of separation on the airfoil has to be prescribed using information from experiments or other means. More recently, low-order methods based on discrete vortices have been developed by Ansari et al, 19 Wang & Eldredge, 20 Ramesh et al 21 to model leading edge vortices in unsteady flows, with applications toward insect flight and MAV aerodynamics. Though these methods are based on potential theory, they capture the essential physics in flows of interest by combining inviscid theory with discrete-vortex shedding.…”
mentioning
confidence: 99%
See 1 more Smart Citation